Evaluation and optimization of functional and antinutritional properties of aquafaba. Issue 2 (23rd January 2020) - Alsalman, Fatemah B.; Tulbek, Mehmet; Nickerson, Michael; Ramaswamy, Hosahalli S.
Abstract: Egg protein is responsible for the second most serious of all food allergens, which affects predominantly the children. Therefore, a new type of vegan ingredient called "aquafaba, " is getting recognized as a plant‐based emulsifier in many bakery product preparations instead of the conventionally used egg white and is emerging in the consumer market. It is the residue water from cooked chickpeas. In this study, an I‐optimal mixture experimental design is combined with a response surface methodology to evaluate the chickpeas cooking process for obtaining aquafaba. The following variables were used: chickpea to cooking water ratio (CPCWR; 1:2, 1:4, and 2:3) and cook time (15, 30, 45, and 60 min). The principal goal was to maximize the functional properties and protein content, while minimizing tannin and phytate contents of aquafaba. The results showed that both CPCWR and cooking time had significant effect on the responses. Emulsion properties were the maximum at 2:3 CPCWR and cooking time of 60 min. Foaming capacity was highest (120%) at 2:3 CPCWR cooked for 30 min, whereas the foam was most stable (57 min) at 1:2 CPCWR with 45 min cooking. Water holding capacity reached the maximum level when cooked for 15 min, and oil holding capacity maximum was obtained after 60 min cooking. Polynomial models were developed for all 11 responses. Optimal results were achieved under the following conditions: 1.5:3.5 CPCWR and 60 min cook time, and the overall desirability fraction was 0.81. Validation tests confirmed these results.